Optical spectroscopy techniques can accurately distinguish benign and malignant renal tumours. (31st August 2012) - Couapel, Jean‐Philippe; Senhadji, Lotfi; Rioux‐Leclercq, Nathalie; Verhoest, Grégory; Lavastre, Olivier; de, Renaud; Bensalah, Karim
<x xml:space="preserve">Abstract</x> What's known on the subject? and What does the study add? There is little known about optical spectroscopy techniques ability to evaluate renal tumours. This study shows for the first time the ability of Raman and optical reflectance spectroscopy to distinguish benign and malignant renal tumours in an ex vivo environment. We plan to develop this optical assistance in the operating room in the near future. Objective To evaluate the ability of Raman spectroscopy (RS) and optical reflectance spectroscopy (ORS) to distinguish benign and malignant renal tumours at surgery. Materials and Methods Between March and October 2011, RS and ORS spectra were prospectively acquired on surgical renal specimens removed for suspicion of renal cell carcinoma (RCC). Optical measurements were done immediately after surgery. Optical signals were normalised to ensure comparison between spectra. Initial and final portions of each spectrum were removed to avoid artefacts. A support vector machine (SVM) was built and tested using a leave‐one‐out cross‐validation. Classification scores, including accuracy, sensitivity and specificity were calculated on the entire population and in patients with tumours of <4 cm. Results In all, 60 nephrectomies were performed for 53 malignant tumours (41 clear‐cell, eight papillary and four chromophobe carcinomas) and seven benign tumours (four oncocytomas, two angiomyolipomas and a haemorrhagic cyst). In all, >700 optical spectra were obtained and submitted to SVM classification. The SVM could recognise benign and malignant renal tumours with an accuracy of 96% (RS) and 88% (ORS) in the whole population and with an accuracy of 93% (RS) and 95% (ORS) in the present subset of small renal tumours (<4 cm). Histological subtype could be determined in 80% and 88% of the cases with RS and ORS, respectively. The SVM was able to differentiate chromophobe carcinomas and benign lesions with an accuracy of 96% in RS and 98% in ORS. Conclusion Benign and malignant renal tumours can be accurately discriminated by a combination of RS and ORS. In vivo experiments are needed to further assess the value of optical spectroscopy techniques.